Interface of Social Media and Financial Products: An Integrative Literature Review - Bhateja , Fiza (Gyan Management Journal, 2023)
INTRODUCTION AND PURPOSE OF THE STUDY: This study delineates the primary domains and existing dynamics of the inter face between social media and financial products suggesting future research directions. Going beyond the mere traditional forms of mar keting, this integrative review covers the research on social media marketing specifically in terms of providing assistance, usage to the consumers with regards to financial products and financial innova tions which ultimately fosters the financial development of a nation. The purpose of this integrative literature review is to propose a frame work for using social media as a tool for marketing, consumer man agement, and financial product promotion. RESEARCH OBJECTIVE: The objective of this integrative literature review is to develop a comprehensive framework that highlights the potential of utilizing social media as a strategic instrument for marketing, consumer management, and promoting financial products. RESEARCH METHODOLOGY: The study conductedantegrative literature review utilizing the Scopus databases, encompassing publi cations up to May 2023. This review included articles from the fields of marketing, decision sciences, finance, and economics. The analy